Social Networking Site Usage and Its’ Impact on Depressive Symptoms among Older Men and Women in South Korea - Jeon, Gyeong-Suk (Int J Environ Res Public Health, 2020)
Background: We examined the rate of social networking site (SNS) usage and the relationship between SNS usage and depressive symptoms among older men and women in South Korea. Methods: The data were obtained from the Living Profiles of Older People Survey (LPOPS), which comprises a nationally representative sample of non-institutionalized Korean older adults living in the community. A total of 10,073 older persons (4286 men and 5787 women) were included in the analysis. Results: A total of 26.0% of the total study population reported to use social network sites. Of the men and women, 32.6 and 21.1%, respectively, used SNS. A higher educational level and higher equivalent household income, lower number of chronic illnesses, no limitation in daily activities, living with others, and having good relationships with friends and neighbors were associated with higher SNS usage among older men and women. SNS usage was significantly associated with reduced depression scores in older men, but not in women. Conclusions: The difference in SNS usage between older men and women might be partially explained by differential exposure to digital technologies and disadvantages in education and economic opportunities. Education programs for digitalization and opportunities to engage with technology need to be provided.